34 Immunologic Evaluation of the Patients With Ranitidine Anaphylaxis - Jin, Hyun-Jung (World Allergy Organization Journal, 2012)
BACKGROUND: There have been a few reports of hypersensitivity reactions to Ranitidine and cross-reactivities between H2-receptor antagonists. The pathogenic mechanisms of H2 receptor antagonist induced hypersensitivity reactions are not understood. The purpose of this study was to observe the clinical characteristics of the patients with Ranitidine anaphylaxis and investigate the pathogenic mechanisms with detection of serum specific IgE antibody to Ranitidine-HSA conjugate. METHODS: Ten patients with anaphylaxis to Ranitidine were enrolled from Ajou University Hospital and Seoul National University Bundang Hospital. Skin prick test (SPT) using Ranitidine extract were performed in 7 patients. Serum specific IgE and G1 antibodies were detected by ELISA using Ranitidine-HSA conjugate. The study subjects were divided into 2 groups according to the presence of serum specific IgE antibody to Ranitidine-HSA conjugate: 3 subjects had high serum specific IgE (Group I) and 7 subjects showed negative results (Group II), when positive cut off value was determined from mean + 3 SD of absorbance values of healthy controls. RESULTS: Six (60%) were female and 9 (90%) were atopics. 6 (86%) patients had positive responses to ranitidine on SPT, however, high serum specific IgE to Ranitidine-HSA conjugate was detected in only 3 patients (30%), while serum specific IgG1 was detectable in one patient (10%). There were no significant differences in clinical characteristics including age, sex, atopy and serum total IgE level between group I and II. CONCLUSIONS: We confirmed the presence of serum specific IgE to Ranitidine-HSA conjugate by ELISA, suggesting that IgE mediated response is a major pathogenic mechanism of Ranitidine induced anaphylaxis. Further studies will be needed to investigate other immunologic and non-immunologic mechanisms and cross-reactivity among other H2 receptor antagonists.